Prognostic Factors and a Nomogram Predicting Overall Survival and Cancer-Specific Survival for Patients with Collecting Duct Renal Cell Carcinoma - Ruotao Xiao (Hindawi Limited, 2021)
Background. Collecting duct renal cell carcinoma (CDRCC) is a rare type of renal cancer characterized by a poor prognosis. The aim of this work was to develop a nomogram predicting the overall survival (OS) and cancer-specific survival (CSS) for patients with CDRCC. Methods. A total of 324 eligible patients diagnosed with CDRCC from 2004 to 2015 were identified using the data from the Surveillance, Epidemiology, and End Results (SEER) database. The Kaplan-Meier curve was used to estimate the 1-, 3-, and 5-year OS and CSS of these patients. Univariate and multivariate Cox regression models were performed to identify the independent risk factors associated with OS and CSS. The nomogram was developed based on these factors and evaluated by the concordance index (C-index) and calibration curves using the bootstrap resample method. The predictive accuracy of the nomogram was also compared with the manual of the American Joint Committee on Cancer (AJCC). Results. The estimated 1-, -3, and 5-year OS and CSS rates in the analytic cohorts were 56.4% and 60%, 32.5% and 37.3%, and 28.7% and 33.6%, respectively. The multivariate model revealed that age, tumor size, tumor grade, N stage, M stage, surgical type, and chemotherapy were independent predicted factors for OS, while tumor size, tumor grade, N stage, M stage, surgical type, and chemotherapy were independently linked to CSS. A nomogram was developed using these factors with relatively good discrimination and calibration. The C-index for OS and CSS was 0.764 (95% CI: 0.735~0.793) and 0.783 (95% CI: 0.754~0.812), which was superior to the AJCC stage (C-index: 0.685 (95% CI: 0.654~0.716) and 0.703 (95% CI: 0.672~0.734)). Patients were divided into low-risk, intermediate-risk, and high-risk groups according to the total points calculated by the nomogram. Patients in the low-risk group (97 mo and not reached) experienced significantly long median OS and CSS compared to the intermediate-risk (17 mo and 18 mo) and high-risk groups (5 mo for both). The calibration curves showed a good agreement between the predicted and actual probability related to OS and CSS. Conclusion. CDRCC has an aggressively biologic behavior with relatively poor prognosis. A survival prediction nomogram making an individualized evaluation of OS and CSS in patients with CDRCC was presented, potentially helping urologists to make a better risk stratification.